High cortisol awakening response and cortisol levels moderate exposure-based psychotherapy success. (January 2015) - Meuret, Alicia E.; Trueba, Ana F.; Abelson, James L.; Liberzon, Israel; Auchus, Richard; Bhaskara, Lavanya; Ritz, Thomas; Rosenfield, David
Highlights: Laboratory studies have shown that glucocorticoids can promote extinction processes. Predictive value of cortisol is examined in naturalistic, exposure study. Cortisol levels and cortisol awakening response act as learning enhancer. Summary: Background: Research suggests that elevated stress hormones during exposure can facilitate fear extinction in laboratory settings. However, prospective studies on the clinical benefits of endogenous cortisol on clinical improvements in naturalistic exposures are lacking. Methods: Twenty-six patients with panic disorder and agoraphobia completed three weekly in-vivo exposure sessions and a fourth session 2 months following therapy completion, resulting in a total of 94 in-vivo exposure sessions. Salivary cortisol was collected at multiple times during the first exposure day (cortisol morning response, prior, -during, -after exposure) and at subsequent exposure sessions (prior, -during, -after exposure). Cortisol collection on a non-exposure comparison day followed the same time schedule as session 1. Results: Exposure day anxiety and cortisol levels were significantly higher than control day levels. Higher absolute cortisol levels during exposures moderated clinical improvement (avoidance behavior, threat appraisal, perceived control). Therapeutic gains were not just related to exposure day cortisol levels, but were also linked to non-exposure day levels. Greater morning rises in cortisol on exposure day predicted greater treatment gains, but greater rises on the control day were associated with poorer outcomes. Conclusions: The study provides first evidence for a moderating effect of cortisol awakening response and absolute cortisol levels on fear extinction processes during naturalistic, prospective exposure-therapy. Additionally, we replicated and extended prior findings on the therapeutic benefits of high exposure cortisol levels. Together, the findings suggest that cortisol may act as a general moderator of facilitated learning during exposure therapy.